Mark assessment of natural potential of landscapes (on the example of the steppe province of Stavropol Plateau) - Pavel Anatolyevich Didenko (Наука. Инновации. Технологии, 2022)
The article gives definition, structure and methods of research of natural potential is given; the assessment of natural and resource potential of steppe landscapes is carried out. On the basis of an assessment indicators of usefulness of landscapes for agricultural production is defined.